Sue Ferrara. The Story That Wasn’t but Now Is. How a Journalist Can Lose and Recover a Story - Ferrara, Sue (Young Scholars Grinchenko – Seton International Journal, 2022)
Often journalists receive story assignments that never come to fruition. This narrative recounts the efforts made to tell a story about how New Jersey school districts were addressing the Ukrainian war in classrooms around the state, and why they need to tell that story was so important. That story was never published for the intended audience but is now rewritten for an academic e-publication.